Anti-corruption expertise of draft legislation: the experience of some European countries and Canada (American Journal of Public Diplomacy and International Studies (2993-2157), 2024)
this paper examines the existing mechanisms for detecting and eliminating corruptogenic norms in some European countries, as well as Canada. Examples of the use of the well-known term “anti-corruption expertise of draft legislation”, as well as the lack of its application, which does not exclude the use of anti-corruption expertise mechanisms in the framework of other procedures of the rule-making process, are described. The author considers the positive experience of some countries (Moldova, Lithuania and Canada), the norms of which are proposed to be implemented in national legislation. In particular, the multilevel systems of "filtering" of developed projects, in which both state organizations and the non-state sector take part, deserve special attention. Also, a positive experience is the well-established system of joint work and close interaction between state bodies authorized to conduct anti-corruption expertise of draft regulations, with public organizations representing the interests of the population of certain territories or other persons. At the same time, the opinions of foreign experts are given regarding certain issues in the field of anti-corruption expertise, as well as on the fundamental issues of applying the concept of "anti-corruption expertise of draft legislation" in general. At the same time, the opinion of the author regarding the studied topics and the presented work is given.